1999
DOI: 10.1016/s0306-4522(98)00514-4
|View full text |Cite
|
Sign up to set email alerts
|

Activation and internalization of the μ-opioid receptor by the newly discovered endogenous agonists, endomorphin-1 and endomorphin-2

Abstract: The multiple effects of opiate alkaloids, important therapeutic drugs used for pain control, are mediated by the neuronal miro-opioid receptor. Among the side effects of these drugs is a profound impairment of gastrointestinal transit. Endomorphins are opioid peptides recently isolated from the nervous system, which have high affinity and selectivity for micro-opioid receptors. Since the miro-opioid receptor undergoes ligand-induced receptor endocytosis in an agonist-dependent manner, we compared the ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 32 publications
3
49
2
Order By: Relevance
“…Interestingly, endo-1 has been shown to produce antinociceptive cross-tolerance to morphine whereas endo-2 does not, suggesting potential differences in the mechanisms of tolerance produced by these two ligands. As both endo-1 and endo-2 stimulate receptor internalization (McConalogue et al, 1999), they would both be expected to produce tolerance via a similar mechanism to that of DAMGO. This suggests that tolerance produced by endo-1 and endo-2 may involve differential activation of signaling pathways unrelated to receptor internalization, or alternatively, that the mechanisms of development of tolerance to these ligands are cell type-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, endo-1 has been shown to produce antinociceptive cross-tolerance to morphine whereas endo-2 does not, suggesting potential differences in the mechanisms of tolerance produced by these two ligands. As both endo-1 and endo-2 stimulate receptor internalization (McConalogue et al, 1999), they would both be expected to produce tolerance via a similar mechanism to that of DAMGO. This suggests that tolerance produced by endo-1 and endo-2 may involve differential activation of signaling pathways unrelated to receptor internalization, or alternatively, that the mechanisms of development of tolerance to these ligands are cell type-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…However, differences between the actions of morphine and those of the endomorphins have been noted. For example, endomorphins-1 and -2 bind the MOR at the cell surface and cause rapid internalization, similar to DAMGO, a MOR-specific synthetic peptide agonist (McConalogue et al, 1999), whereas morphine treatment down-regulates MOR membrane density (Zadina et al, 1993) without rapid MOR internalization (Keith et al, 1996;Zhang et al, 1998). It has been suggested that endomorphin-induced MOR endocytosis may be the mechanism for MOR desensitization and down-regulation (Harrison et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, differences between the actions of morphine and those of the endomorphins have been noted. For example, chronic morphine treatment downregulates MOR membrane density (Zadina et al, 1993) without internalization of the MOR (Keith et al, 1996;Zhang et al, 1998), whereas endomorphins-1 and -2 have been shown to cause rapid endocytosis of the MOR (McConalogue et al, 1999).…”
mentioning
confidence: 99%
“…Thus, studies from our laboratory have demonstrated that OR and ␦OR, when coexpressed in the same cells, internalized through partly distinct endocytic pathways and were sorted via different endocytic vesicles (Gaudriault et al, 1997). Endocytosis of both OR and ␦OR was shown to be clathrin-dependent, based on its sensitivity to a variety of clathrin disrupters Trapaidze et al, 1996;McConalogue et al, 1999;Burford et al, 1998). There is now abundant evidence that internalization of OR occurs in neurons as well as in epithelial cells, both in vitro (Sternini et al, 2000;Keith et al, 1998;McConalogue et al, 1999) and in vivo (Sternini et al, 1996;Eckersell et al, 1998;Trafton et al, 2000).…”
Section: Introductionmentioning
confidence: 99%